(3LGeY GdCSQGQs - (3GdCUHgGfj GdWZQGFj, CHh ESeGYjd, eDjO GdOjf, GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO, J(B513(3g`s ((3Ydj OQhjT Ydj Hf TeS GdOjfs)
(3ChdgG (B:s
(3Gddge jGeafM GdCHhGH CdgefG GdQTO hGdUhGH(B...(3hHYO(B...(3abO GfJgi Ednqj Cfc GJNPJ QCj LeghQ GdYhGe(B...(3aj EfcGQ GdUfYI GdTQjaI(B...s
(3BNQgG (B:s
(3eHJhQI GdBNQ, hBNQ GdehLhO efgG ef GdLRA GdKGfj bhdg(B: ...(3hJahM QhM GdLje HGdOGd aJUjQ bhI eDfKI dCf GdLSO Ydi CQHY WHGFY(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B2(3,U(B246s
(3cTa GdXfhf(B:(3L(B1(3,U(B534s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs